Different Aspects of Emotional Awareness in Relation to Motor Cognition and Autism Traits - Huggins, Charlotte F.; Cameron, Isobel M.; Williams, Justin H. G. (Frontiers in Psychology, 2019)
Emotion is inherently embodied, formulated through bodily sensation as well as expressed and regulated through action. Both expressing one’s own emotions and understanding the emotional actions of others are common areas of difficulty in autism. Moreover, reduced emotional awareness is also thought to be problematic in autism, and such difficulties may be mediated by impaired motor cognition. We aimed to examine how intensity of emotional experience and ability to differentiate between one’s own emotions relates to motor empathy and autistic traits. We hypothesized that greater motor cognition would be associated with greater emotional intensity and more refined emotion differentiation. Participants from the general population (N = 160) completed the Actions and Feelings Questionnaire (AFQ), a self-report measure assessing motor cognition, alongside the Broad Autism Phenotype Questionnaire and an emotion elicitation task. Motor cognition was significantly associated with more intense emotional experiences, but not with ability to differentiate between similar emotions. Autistic traits, particularly social aloofness, predicted less emotion differentiation, and lower scores on the animation subscale of the AFQ. We suggest that whereas as intensity of experience may be dependent on sensorimotor representation of emotions, differentiation requires additional cognitive functions such as language understanding. A dissociation between awareness of intensity and differentiation may be critical for understanding emotional difficulties in autism.